2016
DOI: 10.1097/md.0000000000004520
|View full text |Cite
|
Sign up to set email alerts
|

A negative nontreponemal and/or specific antitreponemal IgM test does not exclude active infectious syphilis

Abstract: Background:The diagnostic criteria for active infectious syphilis in the clinic are important matter of controversy and debate. So far, clinicians habitually do use the negative results of the nontreponemal and/or the specific antitreponemal IgM as the evidences of disease-free or active infection-free status.Method:We present a case study involving a patient who was admitted to Zhongshan Hospital because of cerebral infarct. Clinical examination indicated he had a history of latent syphilis with negative nont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…We observed a continual increase in the RPR titre for a period of time following the first BPG treatment, consistent with the finding of Holman et al [13]. Moreover, previous studies showed that a fourfold decline in the RPR titre and even seronegativity in treated patients did not preclude the development of infection [12,14]. These findings suggested that the RPR titre might not be closely related to the treatment efficacy, and we instead recalled a specific feature of syphilis, the appearance of spontaneous resolution.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed a continual increase in the RPR titre for a period of time following the first BPG treatment, consistent with the finding of Holman et al [13]. Moreover, previous studies showed that a fourfold decline in the RPR titre and even seronegativity in treated patients did not preclude the development of infection [12,14]. These findings suggested that the RPR titre might not be closely related to the treatment efficacy, and we instead recalled a specific feature of syphilis, the appearance of spontaneous resolution.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Holman et al found that approximately 20% of patients exhibited an increase of at least one dilution instead of a decrease in the RPR titre during the 14-day following therapy [13]. More surprisingly, we isolated a virulent T. pallidum strain of type 14d/f from the cerebrospinal fluid of a patient with syphilis with a negative serum RPR test after recommended treatment [14]. These findings constantly challenge the concept that 'RPR titres are suitable for monitoring treatment efficacy'.…”
Section: Introductionmentioning
confidence: 68%
“…MIF is a key indicator of central nervous system infection. Studies have shown that the sensitivity of CSF MIF concentration for neurosyphilis diagnosis was 74.42%, and the specificity was 67.74% (42). The MIF level was higher in the CSF of neurosyphilis patients than in syphilis/non-neurosyphilis patients.…”
Section: Macrophage Migration Inhibitory Factor Testmentioning
confidence: 94%
“…It is noteworthy that the criterion of the decline in the RPR titers to assess syphilis or neurosyphilis treatment has been recommended by a few guidelines ( Janier et al., 2014 ; Xiao et al., 2017a ). Nevertheless, a study showed that virulent T. pallidum remained viable in a patient with a negative serum RPR test after treatment ( Lin et al., 2016 ). Recently, Lin et al.…”
Section: Seroassays For Syphilismentioning
confidence: 99%